Investigation of Combined System between Air Source Heat Pump System for Direct Hot Water Supply and Full Fresh Air Conditioning - He Wenfeng; Zhuo Xianrong; Huang Weiyi (Zhileng xuebao)
In order to provide hot water supply for room and full fresh air conditioning for supermarket in a hotel efficiently, combined system between air source heat pump for direct hot water supply and full fresh air conditioning system was designed and implemented, and its matching algorithm was introduced. After using energy storage equipments as hot water storage tanks and cold storage air-conditioner cabinet, and applying PLC system for data acquisition and heat pump heating time control, a solution to the unbalanced load between heating and cooling was proposed. The running state and operating performance in a full year was tested. The results indicated that the system not only satisfied the requirement of hot water supply for room, but also realized the purpose of full fresh air conditioning for supermarket in the hotel. The average synthesis energy efficiency ratio in a year is over 4.7. The practice provided an example of air source heat pump system for combined heating and cooling supply.